Effectiveness of intra-operative and post-operative use of 5-Fluorouracil in trabeculectomy – a randomized clinical trial - Malla, P; Karki, P; Das, H (Nepalese Journal of Ophthalmology, 2010)
Introduction: The success rate of trabeculectomy is limited by postoperative scarring. Objective: To evaluate the effectiveness of intra-operative and post-operative use of 5- Fluorouracil (5-FU) in trabeculectomy Materials and methods: Thirty consecutive eyes undergoing trabeculectomy were randomized systematically into 3 groups of ten patients each. Group A served as a control; in Group B intraoperative 5-FU was used, whereas Group C received post-operative sub-conjunctival 5-FU. The variables studied were pre- and post-operative intraocular pressure, post-operative bleb characteristics and complications. Statistics: Data were evaluated using the SPSS ver 10.0 program. ANOVA, paired t test and chi2 tests were performed. Results: The means of age in years of patients in group A, B and C were 49 ± 9.23, 56.50 ± 8.39 and 52.10 ± 8.96 respectively (p = 0.222). The means of pre-operative IOP in groups A, B and C were 37.80 ±10 mmHg, 42.00 ± 11.22 mmHg and 29.40 ± 12.82 mmHg respectively. The medians of pre-operative anterior chamber depth (ACD) in groups B and C were 3 and 2 in group A according to van Herrick's grading. The mean values of final IOP were 11.90± 3.50, 11.70 ± 4.24, 11.00 ± 2.83 mmHg (p=0.841). The median post-operative anterior chamber depth in all the groups was similar compared to the pre-operative anterior chamber depth (p= 0.510). The final bleb scores in all the groups were similar (p=0.873). Conclusion: The intra-operative and post-operative use of 5-FU in trabeculectomy is almost equally effective in terms of IOP control and bleb characteristics. Keywords: trabeculectomy; 5-Fluorouracil; glaucoma DOI: 10.3126/nepjoph.v2i1.3699 Nep J Oph 2010;2(1):16-25